THE IMPACT OF ATMOSPHERE ON CUSTOMER DINING SATISFACTION AND BEHAVIORAL INTENTION OF 5 RESTAURANTS IN MANADO - Tamburian, Aprilia; Kindangen, Paulus; Tasik, Hizika H.D. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: The development of the restaurant industry is one of the important sectors that influence the growth of national income. The digital era has influenced so many things including customer satisfaction and assessment on a restaurant. This study aims to find out how much the impact of restaurant atmosphere on customer satisfaction and behavioral intention in this digital era. Three dimensions of restaurant atmosphere used in this research, are: facility aesthetics, ambience condition and exterior design. This study employs path analysis, investigates the direct and indirect effects of restaurant atmosphere on customer satisfaction and behavioral intention with 100 customers as respondents of 5 restaurants in Manado. Results indicate that restaurant atmosphere has positive and significant influence toward customer satisfaction, but it has no direct influence toward behavioral intention. Customer dining satisfaction has positive and significant influence toward behavioral intention. Customer dining satisfaction play an important role as intervening variable. Restaurants have to pay more attention about their restaurant atmosphere to increase the customers satisfaction in order to create their behavioral intention.Â Keywords: restaurant atmosphere, facility aesthetics, ambience condition, exterior design, customer dining satisfaction, customer behavioral intention